Pupil Memoirs as Hagiography in the Gurdjieff Work. Issue 2 (1st February 2022) - Cusack, Carole M.
Abstract : G. I. Gurdjieff (c. 1866–1949) emerged as a spiritual teacher in St Petersburg and Moscow in 1912. In his early phase of teaching, he emphasized a complex cosmology that was recorded by P. D. Ouspensky in In Search of the Miraculous (1949), and after leaving Russia during the Revolution he introduced the Movements or Sacred Dances in Tiflis in 1919. At the Institute for the Harmonious Development of Man at the Prieuré des Basses-Loges at Fontainebleau-Avon south of Paris Gurdjieff initiated a communal life in which pupils pursued a program of spiritual activities devised to lead them from false personality to true self, from a multitude of "I"s to a "real I." After Gurdjieff's death in 1949, various of his pupils published memoirs of their time with the Master; notable examples include Margaret Anderson's The Unknowable Gurdjieff (1962) and Kathryn Hulme's Undiscovered Country: A Spiritual Adventure (1966). This article argues that the pupil memoirs function in the Work as hagiography, cementing the holiness and authority of Gurdjieff in a similar way to the lives of the saints in medieval Europe; additionally, they operate as a substitute for the personal encounter with Gurdjieff in life, constructing his charisma and extraordinary powers for later generations of pupils.